Oversold and underused : computers in the classroom - Cuban, Larry (Harvard University Press, 2001)
"We have to keep ahead in the global economy. The best schools have the most sophisticated computers. Our kids can't be left behind. Our kids need the best. For the last twenty years, many educators, public officials, and business leaders have argued that to keep ahead, American children need to be computersavvy from early childhood onward. Using computers and the Internet in school will give kids a huge academic advantage and, in the long term, prepare them to be winners in an ever more competitive workplace. Real estate agents and parents cite the number of computers in their local schools to demonstrate the quality of their children's education. But just how much of this is true? in Oversold and Underused, one of the most respected voices in American education argues that when teachers are not trained to use new technology, or given a chance to develop creative uses for it in schools, computers end up being just souped-up typewriters. Synthesizing all the research now available, and drawing on his own studies of early childhood, high school, and university classrooms in Silicon Valley, Larry Cuban found that students and teachers use the new technologies far less in the classroom than they do at home and that most classroom use is unimaginative. Even in the heartland of the new technology, classrooms run much as they did a generation ago: they just have new expensive toys in the corner."--Jacket